Spontaneous Apoptosis, Oxidative Status and Immunophenotype Markers in Blood Lymphocytes of AIDS Patients - Gabriele A. Losa; Riccardo Graber (Analytical Cellular Pathology)
Peripheral blood mononuclear cells (PBMC) from 251 HIV‐positive drug abusers of known clinical stage and from 40 healthy donors were tested for conventional immunologic markers (CD3, CD4, CD8, CD19, CD14, CD16/CD56, CD45 and HLA‐DR). Additional cell parameters and the occurrence of spontaneous apoptosis (programmed cell death) were investigated on freshly isolated PBMC by flow cytometric measurement of either annexin‐V bound to plasma membrane phosphatidylserine or propidium iodide uptake. The activity of γ‐glutamyltransferase (γ‐GT), an ectoenzyme contributing to the synthesis of the intracellular antioxidant glutathione (GSH) and involved in early apoptosis, was also determined in these cells. Immunocompetent T‐cell counts were lower in HIV+ patients, with the exception of CD8+ and HLA‐DR+ lymphocytes. The external binding of annexin‐V was significantly higher in HIV+ PBMC and occurred in both CD8+ and CD4+ T‐lymphocyte subsets. The activity of γ‐GT, was significantly lower in the PBMC from HIV+ patients, indicating that the redox status of PBMC may be affected in HIV+ individuals. Finally, the most dominant features characterising patients receiving antiretroviral therapy were greater long‐term stability in the distribution of various cell parameters excepted the level of apoptosis.